Using a hybrid software development approach in implementing The Mind Museum's exhibition service management system - BRYANT, CABANTAC (Archīum Ateneo, 2016)
Non-profit organizations are mostly known to be undermanned, and The Mind Museum (TMM) is no different. Employees in the company are either doing cross-post or carry the work load of two to three people. In the case of TMM Exhibition Department, the staff